Safety and effectiveness of a 6‐French MRI conditional pacemaker lead: The INGEVITYTM clinical investigation study results. Issue 10 (23rd September 2017) - Nielsen, Jens C.; Giudici, Michael; Tolasana Viu, Jose Maria; Chew, Engwooi; Sommerijns, Elke; Wold, Nicholas; Evert, Linda; Love, Charles J.; Stein, Kenneth; Olaf, Hedrich
Abstract: Background: The design of pacemaker leads has continued to evolve; ease of lead handling, improved electrical performance, and magnetic resonance imaging (MRI) conditional aspects have become more important, while safety remains critical. The INGEVITY™ family leads was designed to provide MRI conditional aspects, decreased diameter, and improved performance of pacemaker leads. The INGEVITY study is an investigational device exemption trial evaluating the acute and chronic safety and effectiveness of these leads. Methods: Consecutive patients were included in 77 institutions worldwide, where 1, 657 leads (846 right ventricular active fixation leads, 213 right ventricular passive fixation leads, 121 right atrial passive fixation preformed J‐leads, and 477 right atrial active fixation leads) were implanted or attempted in 1, 060 subjects. Results: At 3‐month follow‐up, the electrical performance were: mean pacing threshold 0.67 V at 0.5‐ms pulse width, pacing impedance 773 ohms, mean P‐wave amplitude 4.8 mV, and R‐wave amplitude 16.5 ± 6.5 mV. Over a median follow‐up of 31 months, 93 subjects died and 33 subjects reported lead‐related complications. Lead‐related complication‐free rate from 0 to 3 months and 3 to 12 months for all leads was 98.4% and 99.7%, respectively. The hazard of lead‐related complications was observed to be decelerating over the course of follow‐up (Weibull shape = 0.23). The overall lead dislodgment rate observed in the study was 1.3%, the perforation rate was 0.0%, and the pericardial effusion rate was 0.3%. Conclusions: The clinical performance of the INGEVITY lead demonstrated a high lead‐related complication‐free rate over 12 months of follow‐up and excellent electrical characteristics.